Hypoglycemia is Associated with Increased In-Hospital Mortality in Patients with Liver Cirrhosis; A Nationwide Study - Obeidat, Adham E; Mahfouz, Ratib; Kozai, Landon; Mansour, Mahmoud; Darweesh, Mohammad; Alqam, Ahmad; Shah, Parthav; Murakami, Traci (Archives of Clinical and Biomedical Research, 2022)
Aim: Cirrhosis may cause dysregulation of glucose homeostasis due to abnormalities in metabolism and responses to changes in the blood glucose level. Cirrhotic patients may be more prone to hypoglycemia. Hypoglycemia is associated with poor outcomes in cirrhotic patients with sepsis and may indicate a greater severity of illness. This study aims to elucidate the effect of hypoglycemia on in-hospital mortality in cirrhotic patients. Methods: This review was completed using the National Inpatient Sample (NIS) database from 2016 to 2019. Using ICD-10-CM codes, we identified patients carrying a diagnosis of cirrhosis and hypoglycemia and gathered baseline demographic and clinical data. Odds ratios (OR) for comorbidities were calculated. Diabetic patients were excluded from the study to rule out the possibility of iatrogenic hypoglycemia. Results: Out of 1,778,829 inpatients with cirrhosis, 31,615 had a diagnosis of hypoglycemia. Total hospital charges were significantly higher in the cirrhosis and hypoglycemia group compared to the non-hypoglycemia group. The mean length of stay (LOS) in the hypoglycemia group was significantly higher. Mortality, vasopressor usage, mechanical ventilation, cardiac arrest, and intensive care unit (ICU) admission were significantly higher in the hypoglycemia group compared to the non-hypoglycemia one. Conclusion: In patients with cirrhosis, hypoglycemia was associated with higher in-hospital mortality and rate of critical illness as suggested by elevated rates of ICU admission, mechanical ventilation, and vasopressor use. These patients also had longer hospital LOS and higher total hospital charges. Hypoglycemia may reflect advanced liver disease or indicate early sepsis and potentially forbodes a prolonged, complicated hospital cours